Electrospun nanofiber of cobalt titanate perovskite as an enhanced heterogeneous catalyst for activating peroxymonosulfate in water. (31st August 2017) - Lin, Kun-Yi Andrew; Lin, Tien-Yu; Lu, Yi-Chun; Lin, Jyun-Ting; Lin, Yi-Feng
Graphical abstract: Highlights: CoTiO3 nanofiber (CTONF) is prepared using the electrospinning technique. CTONF is used as a heterogeneous catalyst for activating PMS to degrade Amaranth. CTONF exhibits a higher catalytic activity than conventional CTO for activating PMS. Both sulfate and hydroxyl radicals are generated from CTONF-activated PMS. CTONF can be reused for multiple cycles to activate PMS for Amaranth degradation. Abstract: As perovskite-type metal oxides are attractive catalysts for activating peroxymonosulfate (PMS), cobalt titanate (CoTiO3 (CTO)) is particularly promising as CTO consists of earth-abundant Ti and Co is the most effective metal for PMS activation. However, conventional preparation methods of CTO result in large CTO aggregates, leading to very low surface area and porosity, and also limiting its performance. In the present study, an electrospinning technique is employed to prepare CTO nanoscale fiber (CTONF), which can exhibit a consistent nanoscale fibrous morphology, enabling CTO to exhibit a relatively large surface area and porosity, as well as mesoporous structures. Thus, CTONF shows a higher catalytic activity than the bulk CTO for activating PMS to degrade a model toxicant, Amaranth (AR) dye. The PMS activation behaviors are further investigated by examining the effects of temperature, pH, and NaCl on AR degradation by CTONF-activated PMS (CTONF-PMS). Through the effects of probe reagents, the AR degradation mechanism can be attributed primarily to sulfate radicals and hydroxyl radicals to a lesser extent. CTONF was also proven to activate PMS over multiple cycles without regeneration. These results reveal that CTONF is a high effective and recyclable heterogeneous catalyst for PMS activation as it outperforms the conventional bulk CTO. The findings obtained in this study also demonstrate that the electrospinning technique can be utilized to prepare perovskites with enhanced physical and chemical properties for catalytic advanced oxidation applications.